Increase in Artillery of the Poltava Fortress in Winter 1708 – Spring 1709 - Sergey A. Ivanyuk (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2020)
Introduction. The battle of Poltava on June 27, 1709 is one of the most famous battles of the Great Northern War. Despite the rich historiography, a number of issues related to this event remain insufficiently studied. This study is devoted to the analysis of certain aspects associated with the formation of the artillery park of the fortified city of Poltava in winter 1708 – spring 1709, the day before and during the siege of the Swedish army.